UEDGE-predicted impact of molecules on low-field side target detachment in DIII–D. (May 2019) - Holm, A.; Groth, M.; Rognlien, T.D.
Highlights: Energy equation implemented in UEDGE to determine the molecular temperature. Qualitative UEDGE - DIII-D experiment agreement improved when solving the molecular energy equation. An X-point MARFE is predicted by UEDGE when considering molecules. Abstract: The impact of fluid molecules on detachment was studied using the edge fluid code UEDGE for a set of DIII–D L-mode plasmas with varying degree of low-field side (LFS) target detachment. A baseline atom-only, fluid-neutral model was compared to models including diffusive deuterium molecules with user-defined molecular temperatures and molecular temperatures solved via an energy equation, respectively. The UEDGE simulations including molecules with their temperature solved via the molecular energy equation displayed improved qualitative agreement with DIII–D measurements. However, at LFS separatrix electron densities below 1.3 × 10 19 m − 3 the LFS target peak electron temperature was over-estimated compared to the DIII–D measurements by a factor of 1.5–2. Kinetic effects, as the SOL collisionalities for LFS separatrix electron densities below 1.3 × 10 19 m − 3 are ν S O L * ≲ 15, could contribute to this discrepancy. At LFS separatrix electron densities above 1.5 × 10 19 m − 3 UEDGE predicted LFS target peak ion current and electron densities a factor up to ∼ 4 lower than the DIII–D-measured values for all models. The consideration of molecules in UEDGE simulations induced a stable X-point MARFE, while an X-point MARFE was not achieved with the ion-atom model. The X-point MARFE forms due to a high-density front which connects the high-field side (HFS) and LFS divertor legs over the X-point, and is not observed for the atom-only UEDGE simulations. The high-density front forms due to molecular particle dynamics and cross-field drifts increasing the plasma density towards the X-point in the HFS leg.